Pemphigus vulgaris in a neonate born to a mother with pemphigus vulgaris: A case report - Ayush Anand; Praneet Awake; Anand Bhosale; Rajan Bindu; Anjali Kher; Prasad Bhanap (Clinical Case Reports, 2023)
Key Clinical Message Active pemphigus vulgaris in the mother can lead to neonatal pemphigus vulgaris, which is usually self‐limiting. Systemic corticosteroids are the mainstay of managing PV during pregnancy and until the child is breastfed. Abstract Pemphigus vulgaris (PV) is a potentially life‐threatening autoimmune disease characterized by bullae and erosions over the skin and mucous membrane. PV is rarely reported in pregnant women and neonates. We reported the case of a 28‐year‐old Gravida 2 Parity 2 Living 1 who developed painful blisters and erosions in the oral cavity during third trimester of pregnancy. However, the diagnosis was delayed due to late presentation. The patient presented to our hospital at 37 weeks gestation with bullae and erosions distributed all over the body. Based on clinical evaluation and histopathology reports, she was diagnosed with PV. She delivered a child via cesarean section. The child also had similar lesions and was diagnosed with neonatal PV. Maternal PV was managed with prednisolone followed by azathioprine, leading to complete remission. No active intervention was required for neonatal PV as the condition was self‐limiting.